Determinants to knowledge transfer and sharing in multimedia super corridor in Malaysia : the mediating role of trust - Meddour, Houcine (2016)
The increased quest for vision 2020 has certainly meant that the role of MSC status organizations in Malaysia in contributing success becomes the subject of considerable debate. In this context, not much research has been conducted on knowledge transfer and sharing in MSC status organizations as well as the mediating role of trust in enhancing knowledge transfer and sharing in the Malaysian organizations. Based on knowledge creation theory, this study examines the determinants of knowledge transfer and sharing in MSC status organizations in Malaysia. Primarily, this study explored the relationship between organizational capacity, organizational motivation, organizational environment, trust and knowledge transfer and sharing in MSC status organizations. Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the hypotheses. The results indicated that eight out of twenty-five hypotheses were found to be positive and significant. Specifically, the hypothesized direct relationships between organizational capacity (top management support), organizational motivation (culture), organizational environment (information technology), trust and knowledge transfer and sharing were supported. The results also revealed that the direct relationships between organizational capacity (human resource practices), and organizational environment (information technology, networks) were significantly related to trust. Furthermore, in terms of trust as mediating variable between organizational capacity, organizational motivation, organizational environment and knowledge transfer and sharing, one out of eight hypotheses indicated full mediation including the relationship between networks and knowledge transfer and sharing. These results offer theoretical, methodological, and practical implications and will help academics and practitioners in the knowledge management field. Nonetheless, further studies are necessary both to confirm the findings and to incorporate additional variables that may influence results. The results of the study were crucial to be looked into so that MSC status organizations could have a clearer understanding and guidelines if they were to enhance their mission to accomplish phase three 2011-2020 of vision 2020 in transforming Malaysia into a knowledge-based society.